Results of the AHOD0431 trial of response adapted therapy and a salvage strategy for limited stage, classical Hodgkin lymphoma: A report from the Children's Oncology Group. Issue 15 (8th May 2018) - Keller, Frank G.; Castellino, Sharon M.; Chen, Lu; Pei, Qinglin; Voss, Stephan D.; McCarten, Kathleen M.; Senn, Stacy L.; Buxton, Allen B.; Bush, Rizvan; Constine, Louis S.; Schwartz, Cindy L.
Abstract : BACKGROUND: The Children's Oncology Group AHOD0431 study evaluated a response‐directed treatment paradigm in which minimal initial chemotherapy and low‐dose radiation was received only by patients who did not achieve a complete remission, and a chemotherapy/low‐dose radiation salvage regimen was received by those who had a protocol‐defined, low‐risk recurrence. METHODS: Patients younger than 21 years who had stage IA or IIA nonbulky disease were eligible. The treatment strategy was evaluated by determining the proportion that received minimal chemotherapy alone, the proportion that had a first or second remission without the receipt of high‐dose chemotherapy/stem cell rescue or higher dose involved‐field radiation therapy (>21 grays), and overall survival. RESULTS: In total, 278 patients were eligible. At 4 years, 49.0% had received minimal chemotherapy and no radiation, 88.8% were in remission without receiving high‐dose chemotherapy with stem cell rescue or >21 grays of involved‐field radiation therapy, and the overall survival rate was 99.6%. Patients who had mixed cellularity histology had a 4‐year event‐free survival (EFS) rate of 95.2%, which was significantly better than the 75.8% EFS for those who had nodular sclerosis histology ( P = .008). A red blood cell sedimentation rate ≤20 mm/hour and a negative fluorodeoxyglucose‐positron emission tomography scan after 1 cycle of chemotherapy (PET1) were associated with a favorable EFS outcome. The study was closed early when the receipt of radiation therapy exceeded the predefined monitoring boundary. CONCLUSIONS: This limited chemotherapy response‐based approach was successful in patients who had a negative PET1 result, had MC histology, or had a low red blood cell sedimentation rate. In this treatment paradigm, evaluation of increased chemotherapy intensity or the integration of active new agents is indicated for patients who have nodular sclerosis histology with a high ESR or who have a positive PET1 result. Cancer 2018. © 2018 American Cancer Society . Abstract : A limited chemotherapy approach is successful in patients with Hodgkin lymphoma who have either a negative fluorodeoxyglucose‐positron emission tomography scan after 1 cycle of chemotherapy or mixed cellularity histology. Eighty‐eight percent of patients are treated without undergoing stem cell transplantation or receiving greater than 21 grays of involved‐field radiation therapy.